Evaluasi Keberhasilan Implementasi Sistem Informasi Perdagangan Daerah Berbasis HOT-Fit dan Technology Acceptance Model - Dzalfa Tsalsabila Rhamadiyanti; Aditya Ahmad Fauzi; Fithriawan Nugroho (JSAI (Journal Scientific and Applied Informatics), 2026)
The Pangkalpinang City Trade Information System (SIPGK) was developed as a digital instrument to support trade data management and data-driven public information services. This study aims to evaluate the implementation success of SIPGK using the Human–Organization–Technology Fit (HOT-Fit) model, with the Technology Acceptance Model (TAM) employed as a complementary interpretative lens. A qualitative evaluative approach was applied through observation, interviews, and system documentation. The results indicate that the technology aspect demonstrates a system availability rate of 95%, reflecting good system quality and service stability, while the organizational aspect is supported by formal policies and standard operating procedures. However, the human aspect remains a key limiting factor due to disparities in digital literacy and data input consistency, along with suboptimal cross-unit data integration. These findings reveal a gap between technological and organizational readiness and human resource capacity in achieving strategic system utilization. The novelty of this study lies in applying the HOT-Fit model to a regional trade information system context, which has been rarely examined, and in integrating TAM as an interpretative framework to explain user acceptance.